Purchase Decisions Reviewed From Brand Image, Price, and Promotion of Alfi Putra BOY Cigarettes - Dwi Anggana, Zulhasnie Yogi; LEKSONO, PONIRAN YUDHO (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: this study aims to find out the Purchase Decision in Review of Brand Image, Price, and Promotion partially and simultaneously Against Alfi Putra BOY Cigarettes Design/Method/Approach: this study uses a quantitative method with a causal approach. With a population of 40 respondents for Alfi Putra BOY cigarette consumers. The data analysis technique of this study uses classical assumption tests, multiple linear regression tests, determination coefficients, and hypothesis tests with SPSS software Research Findings: The results of this study show that brand image and price have a significant influence on purchase decisions partially, while promotion does not show a significant influence partially. Simultaneously, these three variables have a significant influence on purchase decisions. Theoretical contribution/originality: this study provides insight that promotion is not always a significant determining factor, depending on the context of the product and the market. This underscores the importance of adapting marketing strategies according to the characteristics of local consumers. Practitioner/Policy Implications: This research highlights the importance of strengthening brand image through consistent branding and increased product visibility. Competitive pricing proves to be a significant factor in purchasing decisions, so market analysis is necessary to determine attractive prices and reflect the value of the product. Even though promotion is less significant, a creative promotion strategy is still needed. Research limitations: This study is limited to a small sample size, namely 40 respondents, and the coverage of the area only includes Wonodadi village, Blitar Regency. In addition, the variables analyzed include only brand image, price, and promotion, so other factors that may influence purchasing decisions have not been researched. These limitations can be corrected in advanced research by expanding the samples, regions, and variables of the analysis.